Nutritional Status, Diet Diversity and Feeding Behaviour of Children with Disabilities in Kuantan, Pahang - Jaafar, Nurul Hazirah; Zahari, Nur Zahirah (International Journal of Allied Health Sciences, 2024)
Background: In assessing the growth and development of children, proper nutrition plays a critical role, especially for vulnerable populations like children with special needs or with disabilities. It has long been known that children with disabilities are more likely to experience serious issues related to physical, mental or intellectual challenges that are related to their nutritional status. The purpose of this study is to determine the association between dietary diversity and nutritional status of children with disabilities in Kuantan, Pahang. Methods: A cross-sectional study was conducted involving 68 pairs of caregivers and children aged 3 to 18 years from four selected community-based rehabilitation centres in Kuantan. Online questionnaires were used to collect data on their sociodemographic information and children's eating behaviour. Anthropometric measurements and Individual Dietary Diversity Scores (IDDS) were determined on-site. Independent t-test was used to compare diet diversity and feeding behaviour between genders, whereas chi-square test was carried out to establish association between nutritional status and diet diversity. Data were analysed using the Statistical Package for the Social Sciences (SPSS) version 29.0. Results: This study found that 37% of the children were underweight, 57% were stunted, 16% were wasted and 13% were overweight/obese. Approximately 10% of the children had low dietary diversity while 90% had high dietary diversity. Nonetheless, the majority (71%) were identified as picky eaters. Conclusion: There was no association between the nutritional status of children with disabilities and their dietary diversity. Children with disabilities, regardless of high or low diversity were more likely to be underweight and stunted.